Sokrat in sramota - Aubreht, Dejan (Monitor ISH, 2008)
The paper discusses Plato's trilogy Apology, Crito, and Phaedo as Socrates' dialogue with dishonour, which introduces the philosopher's will to death, thereby ascribing a dimension of death to living bodies. Socrates' famous suicide may be understood as a reaction to impending disgrace insofar as the latter is irreducibly bound to the signifier, personified as Socrates' soul. Thus Socrates will save his soul only by keeping the signifier alive, but on the other hand he discusses bodies as the living dead, which leads to a dichotomy fundamental to our Western culture.
Keywords: Socrates, 470-399 pr.n.š.; sram; sramota; telo; duša; subjekt